Age and geochemistry of Late Neoproterozoic and Early Cambrian igneous rocks in southern New Brunswick:: similarities and contrasts - Barr, Sandra; White, Chris; Miller, Brent (Atlantic Geology, 2003)
ABSTRACT Late Proterozoic to Early Cambrian igneous rocks are major components of the fault-bounded Caledonia, Brookville, and New River terranes of southern New Brunswick. As previously demonstrated, ca. 620 Ma and ca. 560– 550 Ma volcanic and plutonic rocks of the Caledonia terrane are petrologically similar to coeval units elsewhere in the Avalon terrane sensu stricto of the northern Appalachian orogen. In contrast, the Golden Grove Plutonic Suite and volcanic rocks of the Dipper Harbour Formation in the Brookville terrane are mainly younger, ranging in age from ca. 555 Ma to 525 Ma. A new U-Pb (zircon) age reported here conﬁrms that rhyolite in the Dipper Harbour Formation crystallized at 553 ± 3 Ma, like the older units of the Golden Grove Plutonic Suite to which they are chemically similar. However, they differ chemically from felsic units of similar age in the Caledonia terrane, with higher K2O and Rb, lower Na2O, and negative epsilon Nd values, although they also appear to have formed in an extensional setting. The Early Cambrian history of the two terranes is also very different, with clastic sediment deposition dominating in the Caledonia terrane while an active continental margin subduction zone developed on the Brookville terrane. A U-Pb (zircon) age of 539 ± 4 Ma shows that volcanic rocks in the Simpsons Island Formation in the New River terrane are early Cambrian, similar to the ages of some plutons of the Golden Grove Plutonic Suite. More petrological studies of the Simpsons Island Formation are needed to assess it tectonic setting and relationship to the older (ca. 555 Ma) Leavitts Head Formation and Ragged Falls Plutonic Suite. These units are chemically similar to one another, consistent with their inferred comagmatic relationship, and are interpreted to have formed in an extensional setting. They are more similar to ca. 555– 545 Ma volcanic and plutonic rocks of the Brookville terrane than to 560– 550 Ma volcanic and plutonic rocks of the Caledonia terrane, although all of these units apparently formed in extensional settings. Too few data are available from volcanic units in the northeastern part of the New River terrane (Lobster Brook Formation) to compare them to the Leavitts Head Formation or to assess their tectonic setting. A U-Pb age of 622 ± 2 Ma from the Blacks Harbour Granite in the southern part of the New River terrane is similar to previously reported ages from the Lingley Suite in the northeastern part of the terrane. More mapping and sampling are needed to deﬁne the extent of these ca. 625 Ma units in the New River terrane and assess their tectonic setting, although a subduction environment is suggested by the available data.